The album [compact disc] (Republic Records, 2023)
The Jonas Brothers took the world by storm in 2019 with the surprise release of their critically acclaimed and widely successful single Sucker following a six-year hiatus. The triple-platinum single debuted at #1 on Billboard's Hot 100. Their third #1 album, Happiness Begins, went platinum, and they recently celebrated receiving a star on the Hollywood Walk of Fame.